Marriage is not an anti-viral agent' : the transformation of sexual health policy in the initial decade of HIV/AIDS in Ireland - Nolan, Ann Marie (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2014)
The aim of this thesis, based on archival records and semi-structured interviews with key stakeholders, was to assess the extent to which HIV/AIDS may be said to have had a transformative effect on Irish sexual health policy between 1982 and 1992 - the first decade during which Ireland was exposed to this new threat to individual and public health.
Keywords: Social Work and Social Policy, Ph.D.; Ph.D. Trinity College Dublin.